2023
DOI: 10.1021/acs.jafc.2c06563
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and Stereochemistry Characters of Phenolic Antioxidant Product Formation

Abstract: The present study developed a smart and novel strategy to elucidate the linkage and stereochemistry characters during phenolic antioxidant product formation. A series of phenolic isomers or analogues were treated with 2-phenyl-4,4,5,5tetramethylimidazoline-1-oxyl-3-oxide radical, to create 16 antioxidant dimerization reactions in aqueous solution. The products were rapidly identified by ultraperformance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight tandem mass-spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Similar successful instances can also be observed in Figure 4 B,D,E. Apparently, these successes could be attributed to the high selectivity of the molecular formula extraction technology in LC-MS [ 46 ] .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar successful instances can also be observed in Figure 4 B,D,E. Apparently, these successes could be attributed to the high selectivity of the molecular formula extraction technology in LC-MS [ 46 ] .…”
Section: Resultssupporting
confidence: 68%
“…Similar successful instances can also be observed in Figure 4B,D,E. Apparently, these successes could be attributed to the high selectivity of the molecular formula extraction technology in LC-MS [46]. Meanwhile, these successful experiments also showed that (1) the LC-MS technology was applicable for the analysis of these Q-markers.…”
Section: Adulteration Detection Validation Experiments Based On Five ...supporting
confidence: 74%
“…The anti -counterfeiting validation experiment was performed using ultra-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight tandem mass spectrometry (UHPLC-ESI-Q-TOF–MS/MS), an analytic technology inferior to UHPLC-Q-orbitrap MS/MS. The chromatography analysis protocol was based on our previous studies [ 25 , 26 ]; while the MS spectra monitoring was achieved using a Q − TOF − MS/MS apparatus (i.e., Triple TOF 5600 plus mass spectrometer, AB SCIEX, Framingham, MA, U.S.A.) [ 27 ]. However, the analytes were 6 counterfeit Wushicha Granules, i.e., CWG 1–CWG 6.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-counterfeiting validation experiment was performed using ultra-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-ight tandem mass spectrometry (UHPLC-ESI-Q-TOF-MS/MS), an analytic technology inferior to UHPLC-Q-orbitrap MS/MS. The analysis protocol was based on our previous studies [24], [25] . However, the analytes were 6 counterfeit Wushicha Granules, i.e., CWG 1 ~ CWG 6.…”
Section: Anti-counterfeiting Validation Experiments Based On 6 Counte...mentioning
confidence: 99%